PERIODIC ANALYSIS OF THE COMPETITIVE DYNAMICS OF TURKISH CIVIL AVIATION IN THE 100TH ANNIVERSARY OF THE TURKISH REPUBLIC - YAŞAR, Mehmet; GEREDE, Ender (Akademik Hassasiyetler, 2023)
The aim of this study is to evaluate the development of Turkish civil aviation in the context of competitive dynamics. The research divides the 100-year history of the Republic into different periods, taking as milestones the major events affecting Turkish civil aviation. The research was based on archival sources, recent industry reports and supported by an extensive literature review. The results of the research indicate the existence of a small number of factors that constitute the dynamics of competition in Turkish civil aviation, which was still in its developmental stage in the early years of the Turkish Republic. During this period, foreign airlines first tried to enter the market through concessions. In the 1930s, the Turkish Airlines State Management Administration (THY) was established, which later continued its activities under the Turkish Airlines brand, and THY continued to exist on its own, except for small initiatives, until the 1980s. This situation led to the continuation of Turkish civil aviation in a monopolistic structure. With the liberalisation movements of 1983 and 2003, the nature of competition changed, the number of airlines increased and the competitive dynamics of the sector started to develop. The research is important in terms of presenting the competitive dynamics of Turkish civil air transport in a systematic way within the history of the Turkish Republic.